MEASURING BANK FINANCIAL PERFORMANCE BETWEEN PRE AND POST ACQUISITION OF BII MAYBANK IN INDONESIA - Sorongan, Marselly (FEB Universitas Sam Ratulangi Manado, 2013)
Banking institutions are one of the key sectors within the financial system. For this reason, the government opens investment opportunities on a large scale to attract foreign investors. This is evident with the increasing number of the Indonesian banking companies which have been taken over by foreign institutions; for instance the acquisition of PT. Bank Internasional Indonesia by Maybank. A Financial report is a tool for analyzing the development of the bank’s performance of pre and post-acquisition. This can be explained by the financial performance in the period of 2005 to 2012. This study uses the ratios on CAMEL method, in capital it use CAR, in quality of the assets it uses AQ Ratio, in Management it uses NPM, for earnings ratio uses ROA and OEOI, and for the liquidity ratio uses LDR. The secondary data is gathered from the Indonesian Stock Exchange (IDX) and Publication Financial Consolidation report from the BII website. Results of statistical tests uses Paired Sample T-tests which concludes that the Financial Performance BII Maybank of the pre-acquisition was better than that of the post-acquisition. Accordingly, the financial performance of PT. Bank Internasional Indonesia Tbk. has no significant difference between pre and post-acquisition. Acquisition activity in the BII Maybank takes more than a 4-year period after the acquisition to yield better results using CAMEL ratio or other financial methods. This study suggests that the financial performance of BII Maybank is affected by their acquisition activity, although the result of post-acquisition is not much better than post-acquisition. Keywords: financial performance, merger and acquisition, CAMEL ratio